A simple time optimal digital control for nuclear reactors - D'Attellis, Carlos Enrique; Lorenzetti, José Raúl; Reyes, Carlos Héctor (North Holland Publishing Co., 1974)
Fil: D'Attellis, Carlos Enrique Comisión Nacional de Energía Atómica; Argentina